Evaluation of the noise level and its effects on the workers of the maintenance and production workshop of the Universidad Nacional del Altiplano, Puno - Sonco Justo, Fanny Marisol (2023)
Noise generated by activities in maintenance and production workshops can cause damage to the hearing system. This research aimed to determine noise levels and their effects on maintenance and production workshop workers during 2018 and 2019. A quantitative, non-experimental and descriptive approach was used. The workshop has four areas dedicated to metalworking, carpentry and melamine. Noise measurements were made in each area and in existing equipment, using a sound level meter in accordance with ISO 1996-Part 1:1986 and IEC 61672-1:2002. For monitoring, the National Noise Monitoring Protocol (D.S. No. 223) and the methodology of the Regulations on Occupational Safety and Health in Mining (D.S. No. 024-2016-EM) were applied. The results showed noise levels of 78.1 dB, 80.8 dB, 78.2 dB, and 78.0 dB in areas PR-1, PR-2, PR-3, and PR-4, respectively, of which only PR-2 exceeded the standard of 80 dB for industrial zones. The evaluation of 27 devices revealed that 93% exceeded 80 dB, reaching up to 107.9 dB. These data indicate a high risk of hearing problems for staff, underscoring the need to monitor exposure time and conduct regular assessments to minimize long-term effects.